Collaboration Between The Government And The Private Sector Through Creative Financing Schemes To Accelerate Regional Infrastructure Development - Yunita Fourina Dewi (STEBIS Bina Mandiri, 2025)
The limited fiscal capacity of regions to support the surge in infrastructure needs in peri-urban areas demands a policy reorientation toward non-conventional funding models. This qualitative research with a descriptive-analytical case study design aims to in-depth analyze the collaboration model between the Bogor Regency Government and the private sector through a creative financing scheme to accelerate regional infrastructure development. Primary data was collected through in-depth, semi-structured interviews with key informants from Bappedalitbang, the Public Works and Housing Agency (PUPR), the Regional Financial and Asset Management Agency (BPKAD), and a consortium of private partners. These were then triangulated with official policy documents and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the creative financing scheme effectively closes the regional budget deficit (funding gap) by leveraging the value of public assets and rationally sharing investment risks without burdening the regional debt balance. The success of this ecosystem is largely determined by the quality of local collaborative governance, where the institutionalization of the Creative Financing Acceleration Team and the involvement of a national guarantee institution are able to reduce bureaucratic obstacles and erode the risk-averse behavior of regional officials due to fear of policy criminalization. This research introduces a novel concept called managed asymmetry, which emphasizes the importance of knowledge transfer from the private sector to compensate for the limited technical competence of civil servants. Practically, this research formulates a blueprint for strengthening regional institutional capacity, leading to the role of civil servants as reliable contract managers. In conclusion, the synergy of local legal certainty, transparent risk mitigation, and political commitment of regional leadership is the main foundation for accountable and sustainable subnational infrastructure acceleration.